Outlook of Precision Farming in Hungary - Popp, József; Erdei, Edina; Oláh, Judit (International Journal of Engineering and Management Sciences, 2018)
For agriculture, precision farming means the future by increasing incomes and reducing environmental loads at the same time Precision management produces a surplus in yield, revenue, result, but not immediately. The additional income potential is expected to increase by 20% to 50%. Farms mostly introduce precision farming in order to relieve workers. However, many farmers are afraid of the use of new technologies, but the use of information technology in agriculture will be unavoidable. Technology is fundamentally expensive, not even widespread, and farmers use only a few technology elements. Moreover, following the precautionary principle technology used in farming covers only a part of their agricultural land. So farms need to learn to produce more precisely than before in a knowledge-based manner.